The quality of mobile operator : students perspective / Noor Azuan Jahaya - Jahaya, Noor Azuan (2006)
This study was carried out to make comparison of quality among service provider and to identify factors that influence students to choose a service provider. For this purpose, questionnaires were distributed to UiTM students from faculties like Information Technology and Quantitative Science, Civil Engineering, Administrative Science and Policy Study, Art and Design, Sport Science and Recreation, Accountancy and Office Management to ensure that comparison of quality can be made and factors can be identify. The study was divided into two stages. The first stage was committed to collecting and analyzing data from questionnaires. The second stage, using same procedure, hypothesis were tested based on the variables in selected theoretical model. The finding show network coverage of quality of services among service provider is very important. Even though respondents are giving chance to switch to another mobile operator, most of them chose to be with the same operator. It is hard to determine which factors will strongly influence respondents in order to choose service provider. If looking at the number of respondents who chose "Strongly Agree", most of respondents chose family and fiiends. This finding confirms past research that said family and fiiends is the most influence persons in an individual life. The findings imply that lot of research need to be made among students because they are higher user of these service provider